Respuesta a la aplicación de bioestimulantes en el cultivo de camote (ipomea batata l) en yascón, cantón Bolívar, Provincia del Carchi - Reyes Yalamá, Lauro Rafael (2011)
Show it investigation province of the Carchi, with evaluating the answer of the sweet potato cultivation to three bioestimulantes foliares's application purpose sold off in Yascón's zone of the canton Bolivar itself; Identifying best-suited treatment and accomplishing the treatments's economic analysis. The planting material utilized was dark purple sweet potato with application of three bioestimulantes foliares in two dose each one, the bioestimulantes were Biopower, Húmico Seguro and Dólar Plus. Utilized him the experimental design once was named Bloques Completos at random with seven treatments and four repetitions, using Tukey's test to the 5. variables evaluated attended : branch Length to the 30; 60; 90 and 120 days elderly of plants; the stem's diameter to the 30; 60; 90 and 120 days; the stem's ramification to the 30; 60; 90 and 120 days elderly; Number, diameter, length and I weigh of the tubers and performance for hectare. conclusions are : The dark purple- sweet potato cultivation, he showed good agronomic behavior to the bioestimulantes foliares Dólar Plus's, Humico Seguro's and Biopower's application in the canton's zone Bolívar, the Carchi's province; The bigger tubers performance of sweet potato was registered with the bioestimulante Dólar Plus in dose of 500 cc/ha.